Las cartas de Franco : la correspondencia desconocida que marcó el destino de España / Jesús Palacios ; prólogo de Stanley G. Payne - Palacios, JesúsPayne, Stanley G.; Franco Bahamonde, Francisco (1892-1975)
Índices: p. [581]-590